2010
DOI: 10.3758/s13414-010-0069-3
|View full text |Cite
|
Sign up to set email alerts
|

Fractal fluctuations in gaze speed visual search

Abstract: Visual search involves a subtle coordination of visual memory and lower-order perceptual mechanisms. Specifically, the fluctuations in gaze may provide support for visual search above and beyond what may be attributed to memory. Prior research indicates that gaze during search exhibits fractal fluctuations, which allow for a wide sampling of the field of view. Fractal fluctuations constitute a case of fast diffusion that may provide an advantage in exploration. We present reanalyses of eye-tracking data collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 68 publications
7
28
0
Order By: Relevance
“…Previous research has documented such findings in the context of exploratory movements by the hand or by the eye (Stephen & Anastas, 2011;. The predictive power of fractality for capturing differences in information detection supports a view of perception-action as the evolving transaction of an organism with the patterned energy distribution in the environment (Gibson, 1966;Wagman & Miller, 2003) without depending on a simple psychophysical correspondence (cf.…”
Section: Temporal Fractality Differed Across Limbs In General and Dursupporting
confidence: 52%
See 1 more Smart Citation
“…Previous research has documented such findings in the context of exploratory movements by the hand or by the eye (Stephen & Anastas, 2011;. The predictive power of fractality for capturing differences in information detection supports a view of perception-action as the evolving transaction of an organism with the patterned energy distribution in the environment (Gibson, 1966;Wagman & Miller, 2003) without depending on a simple psychophysical correspondence (cf.…”
Section: Temporal Fractality Differed Across Limbs In General and Dursupporting
confidence: 52%
“…Sensitivity to events across such a wide variety of scales makes search behavior more thorough and effective (Bartumeus, Catalan, Fulco, Lyra, & Viswanathan, 2002;Reynolds, 2010). Indeed, temporally fractal fluctuations in exploratory movements (by the hand and eye) facilitate the detection of information in perceptual tasks (Dixon, Stephen, Boncoddo, & Anastas, 2010;Stephen & Anastas, 2011;Stephen, Boncoddo, Magnuson, & Dixon, 2009). Most relevant to the present article, temporally fractal fluctuations in wielding movements promote accuracy in judgments during dynamic touch by the hand .…”
Section: Long-range Temporal Correlations In Exploratory Movementsmentioning
confidence: 79%
“…However, the relation between task difficulty and scaling in eye movements is not straightforward. For example, although Stephen and Anastas (2011) showed that faster completion of a visual search task corresponded to increases in scaling exponents, results by Wallot, O'Brien, Coey, and Kelty-Stephan (2015) showed that increases in text difficulty in a reading task also led to an increase of scaling exponents in eye movement fluctuations. While the former finding seems to indicate that a reduction in task difficulty during visual search goes together with higher scaling exponents, the latter finding seems to indicate that an increase in task difficulty during reading goes together with higher scaling exponents.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown fluctuations across fixations and saccades are intimately connected, suggesting that eye movements of all sizes are governed by fundamentally interdependent processes (e.g., Stephen & Mirman, 2010;Wallot, Coey, & Richardson, 2015;Wallot & Kelty-Stephen, 2014). More specifically, like many other kinds of behavioral and physiological measures (see Van Orden, Kloos, & Wallot, 2011 for a review), eye movements display complex patterns of fluctuations that conform to power-law scaling relations (e.g., Aks, Zelinsky, & Sprott, 2002;Coey, Wallot, Richardson, & Van Orden, 2012;Mirman, Irwin, Stephen, 2012;Stephen & Anastas, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation